Cognition based selection and categorization of maintenance engineer (agent) using Artificial Neural Net and Data Mining methods - Mishra A.; Srivastava V. (My University, 2025)
Software maintenance has major problem and it is having great challenges throughout the entire life cycle of software product. A major is selection of maintenance engineer for the general and domain specific knowledge towards the maintenance tasks. This paper is an experimental evaluation and a model has been proposed for Selection of Maintenance Engineer (SME) i.e. an agent. Based on the cognitive and social characteristics such as belief, desire, intention, reliability and reputation, intelligent computing methods such as Artificial Neural Net, Data Mining methods have been deployed in our work. This work can predict the attitude of the agent towards specific maintenance task using these characteristics. In this work, the computation have been done for general and domain specific cognitive behavior of some agents based on data provided and treated those data as testing data for the models generated by using intelligent computing methods. The set of results have found that will help lots towards this context. © 2012 IEEE.